How reverse turns may mediate the formation of helical segments in proteins: an x-ray model. - Perczel, A (1992)
The three-dimensional structure of a protein is the assembly of different secondary structural elements, such as alpha-helices, beta-pleated sheets, and beta-turns. Although the conformation of hundreds of proteins has been elaborated in the solid state, only a vague understanding of the mechanism of their conformational folding is known. One facet of this topic is the conformational interconversion of one or more beta-turns to a helical structure (and vice versa), which may also be related to the formation of helix-turn-helix motifs often observed in globular proteins. Based on a comprehensive structural analysis of proteins, Sundaralingam and Sekharudu [Sundaralingam, M. & Sekharudu, Y. C. (1989) Science 244, 1333-1337] previously suggested that "structure-water" molecules in proteins may mediate such a conformational change. An x-ray crystal structure determination of t-butoxycarbonyl (Boc)-Val-Ser-NHCH3 reveals (i) an ideal type I beta-turn backbone conformation and (ii) a hydrogen-bond network more typical of an alpha-helix than a beta-turn conformation. The molecular packing of this simple beta-turn model reported here provides a plausible and simple alternative of how a beta-turn-like conformation may serve as a conformational template for helical-structure formation (and vice versa) during the folding procedure.